2006
DOI: 10.1590/s0103-50532006000500027
|View full text |Cite
|
Sign up to set email alerts
|

Probing interchain interactions in emissive blends of poly[2-methoxy-5-(2'-ethylhexyloxy)-p-phenylenevinylene] with polystyrene and poly(styrene-co-2-ethylhexyl acrylate) by fluorescence spectroscopy

Abstract: Nesse trabalho foram realizados estudos dinâmicos e estáticos de fotoluminescência de blendas poliméricas do poli[2-metóxi-5-(2'-etilexiloxi)-p-fenileno vinileno] (MEH-PPV) com poliestireno-co-2-co-metacrilato de metila1-1-pirenila e seu copolímero poli(estireno-co-acrilato de 2-etilexila-co-1-metacrilato de metila1-1-pirenila) (com 9 mol% e 19 mol% de unidades acrilato de 2-etilexila unidades e 0,06 mol% de 1-pirenila). O poliestireno marcado com pirenilo e alguns de seus copolímeros foram sintetizados por po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
7

Year Published

2008
2008
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 56 publications
0
4
0
7
Order By: Relevance
“…PVK in dilute THF solution presented a high concentration of excimers, which also indicates that the chains were not completely extended. Consequently, in terms of dimensions, the R g values of these two polymers are much larger than the Förster radius for FRET that is generally observed for conjugated polymers (3–5 nm; 24,50).…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…PVK in dilute THF solution presented a high concentration of excimers, which also indicates that the chains were not completely extended. Consequently, in terms of dimensions, the R g values of these two polymers are much larger than the Förster radius for FRET that is generally observed for conjugated polymers (3–5 nm; 24,50).…”
Section: Resultsmentioning
confidence: 84%
“…According to this model, donors and acceptors are point dipoles with weak interactions; furthermore, the Fo¨rster equation for R 0 requires that the FRET process occur under thermally equilibrated conditions (12). In the literature, studies have reported that the Fo¨rster radius for conjugated polymer blends is in the range of 3-7 nm (6,7,11,17,18,25,26,40,50,54). One methodology for the calculation of R 0 takes into account experimental data such as the overlap integral between the donor emission and the acceptor absorption, the refractive index of the medium, the PL quantum yield of the donor in the absence of the acceptor, and an orientational parameter for the dipole distributions (12,22).…”
Section: Energy Transfer In Filmsmentioning
confidence: 99%
“…Ludox was used as scatterer to register the instrumental response. Deconvolution of the laser pulse was performed, optimizing the random residual distribution to achieve a χ 2 parameter close to unity. , Decays were initially recorded using pulsed diode lasers for excitation (375 and 470 nm) and collected with emission at 550 nm. Experiments of time-resolved emission spectroscopy were performed using the same excitations and tuning the emission from 500 to 700 nm in intervals of 10 nm.…”
Section: Methodsmentioning
confidence: 99%
“…10 The study of the electronic excited state dynamics of conducting polymer using excitation and emission spectroscopy has provided important information about exciton diffusion, migration, trapping and quenching in aggregates like excimers or its deactivation in low energy charge-transfer states. [11][12][13][14][15] These processes are closely related to the luminescence yields and stability of several optoelectronic devices based on conjugated polymers.…”
Section: Introductionmentioning
confidence: 99%